Association of neurologist care with headache expenditures: A population-based, longitudinal analysis. (October 2018) - Ney, John P; Sico, Jason J; Klein, Brad C; Magliocco, Brandon; Callaghan, Brian C; Esper, Gregory J
Objective: To assess the association of neurologist ambulatory care with healthcareutilization andexpenditure in headache. Methods: This was a longitudinal cohort study from two-year duration panel data, pooled from 2002–2013, of adult respondents identified with diagnostic codes for headache in the Medical Expenditure Panel Survey. Those with a neurologist ambulatory care visit in year one of panel participation were compared with those who did not for the change in annual aggregate direct headache-related health care costs from year one to year two of panel participation, inflated to 2015 US dollars. Results were adjusted via multiple linear regression for demographic and clinical variables, utilizing survey variables for accurate estimates and standard errors. Results: Eight hundred and eighty-seven respondents were included, with 23.3% (207/887) seeing a neurologist in year one. The neurologist group had higher year-one mean headache-related expenditures (3032 vs. 1636), but nearly equal mean year-two expenditures compared to controls (1900 vs. 1929). Adjusted association between neurologist care and difference in mean annual expenditures from year two to year one was −1579 (95% CI −2468, −690, p < 0.001). Conclusion: Among headache sufferers, particularly those with higher headache-related healthcare expenditures, neurologist care is associated with a significant reduction in costs over two years.